2022
DOI: 10.1037/pspp0000394
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change of perceived characteristics of major life events.

Abstract: The study design was preregistered at https://osf.io/kvf5g/. The preregistration of the present analyses, the data, and R scripts can be retrieved from https://osf.io/urqdw/?view_only=e97f3517abe8466fb5a1a9dcb430f908. We have no known conflict of interest to disclose. Data collection was funded by Pathways to Character Project (sponsored by the John Templeton Foundation and the Arizona State University Foundation), Grant 60699 to Maike Luhmann.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 119 publications
(273 reference statements)
1
24
0
Order By: Relevance
“…From a methodological point of view, this translates into surveys asking respondents to report only events that were significant for them rather than collecting data on all trivial or ordinary life events using checklists [22,23]. One study recently highlighted the very high rank-order stability and intraclass correlations, as well as the nonsignificant mean-level change of the emotional significance of major life events [24].…”
Section: Valence Emotional Significance and Domain Of Life Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a methodological point of view, this translates into surveys asking respondents to report only events that were significant for them rather than collecting data on all trivial or ordinary life events using checklists [22,23]. One study recently highlighted the very high rank-order stability and intraclass correlations, as well as the nonsignificant mean-level change of the emotional significance of major life events [24].…”
Section: Valence Emotional Significance and Domain Of Life Eventsmentioning
confidence: 99%
“…Second, although we aimed to encompass the period spanning from pre-to post-event, we might have overlooked the actual moment of the event. Indeed, the time span between the occurrence of the event and participation in the study could not be controlled for, which may have affected the strength of the observed effects, even though a recent study showed that the rank orders of most of the major life event characteristics over one year were relatively stable [24]. Hence, future studies could adopt a more dynamic approach by using an intensive longitudinal design.…”
Section: Limitation and Future Directionsmentioning
confidence: 99%
“…All the above-mentioned studies examined the perceived event characteristics at one specific time point after the event (i.e., the perceived event characteristics were used as a fixed predictor of changes in SWB). However, the perception of major life events can change over time (Haehner, Kritzler, et al, 2021), which leads to the question: Are changes in the perception of major life events related to changes in SWB?…”
Section: Changes In the Perceived Event Characteristics And Changes I...mentioning
confidence: 99%
“…Data from the What's NEXT? Study has already been used in previous publications on perceived event characteristics (Fassbender et al, 2021;Haehner, Kritzler, et al, 2021;Haehner, Rakhshani, et al, 2021;Kritzler et al, 2021;Luhmann et al, 2021). However, none of these studies examined the relationship between changes in the perception of major life events and changes in SWB (see Table S1 for more details on the usage of the What's NEXT?…”
Section: Study 1: Exploratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation